ANALYSIS OF THE IMPLEMENTATION OF CASH DISBURSEMENT SYSTEMS AND PROCEDURES OF MAGELANG REGIONAL PEOPLE'S REPRESENTATIVE COUNCIL (DPRD) SECRETARIAT - Abim Aulya; Suci Nasehati Sunaningsih (MESP–FEB UNS, 2020)
Cash disbursement is a series of financing issued for activities that benefit the instance. This study aimed to determine the cash disbursement systems and procedures at the Secretariat Office of the Regional People's Representative Council (DPRD) of Magelang City. The object of this research is the Magelang City DPRD Secretariat. This study used a descriptive method to reveal facts, circumstances, phenomena that occur by comparing the cash disbursement systems and procedures at the DPRD Secretariat with the theoretical concepts of cash disbursement effectiveness. The cash disbursement procedure at the Magelang City DPRD Secretariat is effective and following applicable regulations. The obstacle faced during the cash disbursement process is the sketchy accountability letter (SPJ) submitted for cash disbursement. Keywords: System, State finances, Cash disbursement